2017
DOI: 10.17814/mechanik.2017.8-9.117
|View full text |Cite
|
Sign up to set email alerts
|

The 3D Printer Farm – function and technology requirements and didactic use

Abstract: Historia druku 3D na Wydziale SiMR PWNowo otwarta farma drukarek 3D była pomyślana jako element rozbudowy Laboratorium 3D, działającego od ok. 2008 r. W tamtym czasie w ramach grantu KBN zakupiono profesjonalną drukarkę 3D firmy Stratasys -model Dimension 1200BST (stosujący metodę FDM [2]) oraz optyczny skaner 3D firmy Smarttech, model ScanBright wraz z oprogramowaniem. Laboratorium 3D było i jest wykorzystywane w kształceniu studentów, zwłaszcza na specjalności "Wspomaganie Komputerowe Prac Inżynier-skich" na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Laplume and others [88] develop the idea of a 3D-print shop in a semi-empirical study. They assume a production on-demand BM and a number of configurations of consumer-grade FDM 2 -printers that is, printer farms with several centrally-controlled machines [89]. It has been suggested that printer farms would accrue economically sustainable annual revenues [88].…”
Section: Peer-to-peer Manufacturingmentioning
confidence: 99%
“…Laplume and others [88] develop the idea of a 3D-print shop in a semi-empirical study. They assume a production on-demand BM and a number of configurations of consumer-grade FDM 2 -printers that is, printer farms with several centrally-controlled machines [89]. It has been suggested that printer farms would accrue economically sustainable annual revenues [88].…”
Section: Peer-to-peer Manufacturingmentioning
confidence: 99%
“…In a broad sense, a 3D printing build farm is defined as a collection of similar 3D printers controlled by a central networked system. More advanced build farms may include autonomous systems to monitor production and perform tasks such as removing completed prints from machines, as well as include post-processing capabilities, or they may rely on technicians for these roles (Skawiński & Siemiński, 2017). The minimum number of 3D printers to be classified as a build farm is as low as 3-5 (Laplume, Anzalone & Pearce, 2016;MANUFACTUR3D, 2019), and theoretically can be scaled up infinitely.…”
Section: Background Framing the 3d Printing Build Farmmentioning
confidence: 99%
“…The democratic manufacturing project focused on providing students the opportunity to assemble/manufacture, operate and maintain a 3D printer farm within their product design studio. A 3D printer farm is a large collection of 3D printers situated in one location; an example is the Monkeyfab Prime 3D printers shelved in one location at The Department of Automotive and Machine Tools at the Warsaw University of Technology [1]. 3D printer farms can be framed in two contexts i.e., integrated production, and consumer production.…”
Section: Introductionmentioning
confidence: 99%